2012
DOI: 10.1103/physrevlett.109.180503
|View full text |Cite
|
Sign up to set email alerts
|

Noiseless Loss Suppression in Quantum Optical Communication

Abstract: We propose a protocol for conditional suppression of losses in direct quantum state transmission over a lossy quantum channel. The method works by noiselessly attenuating the input state prior to transmission through a lossy channel followed by noiseless amplification of the output state. The procedure does not add any noise hence it keeps quantum coherence. We experimentally demonstrate it in the subspace spanned by vacuum and single-photon states, and consider its general applicability.PACS numbers: 03.67. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 41 publications
2
103
0
Order By: Relevance
“…It appears especially useful in the context of quantum key distribution, as it has been theoretically shown to improve the key rate of device-independent discrete-variable protocols [13,14] as well as the range and tolerable excess noise of continuous-variable Gaussian protocols [15][16][17]. Interestingly, the combination of a noiseless attenuator and amplifier at the two ends of a communication line provides a means to reduce the line losses without adding noise [8], which can be exploited in quantum key distribution (note that the noiseless amplifier or attenuator does not necessarily need to be realized in practice, but can be emulated via a postselection procedure [16]). …”
Section: Introductionmentioning
confidence: 99%
“…It appears especially useful in the context of quantum key distribution, as it has been theoretically shown to improve the key rate of device-independent discrete-variable protocols [13,14] as well as the range and tolerable excess noise of continuous-variable Gaussian protocols [15][16][17]. Interestingly, the combination of a noiseless attenuator and amplifier at the two ends of a communication line provides a means to reduce the line losses without adding noise [8], which can be exploited in quantum key distribution (note that the noiseless amplifier or attenuator does not necessarily need to be realized in practice, but can be emulated via a postselection procedure [16]). …”
Section: Introductionmentioning
confidence: 99%
“…However in neither of the cases, the entanglement has been restored to the original maximum value due to the presence of the vacuum term |00 00|. Recently, Mičuda et al experimentally demonstrated a rather clever way to eliminate the presence of such term [39]. They considered only vacuum and a fixed polarization single photon state, but the technique can be adopted for qubit amplification as well.…”
mentioning
confidence: 99%
“…Neglecting the noiseless attenuation terms ( [19], which can arbitrarily approach the identity at the limit of a small reflectivity R → 0, the conditional state heralded by one-photon detection is,…”
Section: Basics Of Photon Subtractionmentioning
confidence: 99%